PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN DANA BAGI HASIL TERHADAP ALOKASI BELANJA MODAL (Studi Pada Pemerintah Kabupaten/Kota di Jawa Tengah) - Laras Novitasari; Sri Laksmi Pardanawati; Indra Lila Kusuma (JURNAL WIRANOMIKA, 2024)
This study aims to determine the effect of regional original income, general allocation funds, special allocation funds and profit sharing funds on capital expenditure in Regency/City Governments in Central Java in 2018-2022. The population used in this study were all regencies/cities in Central Java Province, totaling 35 regencies/cities. The sample used in this study is by using a saturated sampling technique (Saturation Sampling), which consists of 35 Regencies/Cities. The data used is in the form of secondary data from district/city APBD reports in Central Java. This study used multiple linear regression analysis with the SPSS 23 program. The results of the analysis showed that the regional original income variable had no effect on capital expenditure with a significance level of 0.607 > 0.05, the general allocation fund variable had an effect on capital expenditure with a significance of 0.025 <0, 05, special allocation funds have no effect on capital expenditure with a significance level of 0.004 <0.05, profit sharing funds have a significant effect on capital expenditure with a significance level of 0.012> 0.05.Keywords: Local Own Revenue, General Allocation Fund, Special Allocation Fund, Profit Sharing Fund, Capital Expenditures